SINTESIS BIODISEL MENGGUNAKAN KATALIS CaO CANGKANG KERANG DARAH: OPTIMALISASI TEMPERATUR REAKSI DAN KALSINASI KATALIS - Zaidi Asyadiqi; Nurhayati '; Muhdarina ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Blood cockle shells (Anadara granosa) can be used as heterogeneous catalysts for biodiesel production because it contains CaCO 3 that can be decomposed into CaO. In this study, blood cockle shells was calcined at temperatures of 800, 900 and 1000 oC for 10 hours. The synthesis of biodiesel was done by transesterification process of cooking oil and methanol. The condition variables for biodiesel synthesis studied were reaction temperatures (55, 60, 65 and 70 °C) and catalyst calcination temperatures (800, 900 and 1000 °C). The optimum of biodiesel results was 71.58 % with catalyst weight conditions of 4 % (w/w), the mole ratio of oil- methanol 1: 6, reaction temperature at 60±2 oC for 3 hours using catalyst calcination at 900 o C for 10 hours. Biodiesel obtained has a water content of 0.031 %, density of 870 kg/m 3 , viscosity of 3.63 mm 2 /s, flash point of 150 oC, carbon residue of 0.029 %, acid number of 0.23 mg KOH/g, iodine number of 50.26 g-I 2 /100 g and cetane number of 67.9. All of the characteristics of biodiesel correspond to the SNI for biodiesel (SNI 04-7182-2006).